PENGARUH TOKOH SUPERVILLAIN DALAM FILM SUPERHERO - Nury, Mekka Syed (Institut Seni Budaya Indonesia Bandung, 2017)
Superhero movie is a film that tells the story of a superhero fight against crime. In the story of his struggle, the superhero character often passes many obstacles for his purpose to stop the ambition of the villain in creating chaos in the world. Analysis of supervillain characters in this paper based on the theory of causality, where in the description, the author tries to compare the results that occur if the character supervillain successfully carry out his ambition with the result that occurs if the supervillain character fails to carry out his ambition, The results of the study can also illustrate how the influence of the supervillain character in the superhero film. There are many criminals that we know from superhero movies. Many also memorable figures such as The Joker, or Loki. Among the many superhero characters, there are some figures who have an interesting ambition, where the ambition will make us curious if the ambition of the villain is achieved. Will that ambition bring life in this world for the better, or even worse.